Pengaruh Counterpressure Dan Tehnik Relaksasi Nafas Dalam Terhadap Nyeri Melahirkan Pada Ibu Bersalin Kala 1 Fase Aktif di Rumah Sakit Dr Hafiz Cianjur Tahun 2023 - Nurul Hidayah Mulyati; Rina Afrina; Siti Kamilah (Lembaga Pengembangan Kinerja Dosen, 2024)
Childbirth is a natural process that every pregnant woman will experience. Most mothers start to feel pain or labor pains during the first active phase. In this phase, most mothers feel severe pain because the uterus begins to become active. In this phase, contractions become stronger and more frequent. One of the duties of a nurse is to assess the condition of pain including the cause of pain, quality of pain, location of pain, how much it interferes with life and the time or duration of pain as well as determining diagnosis, planning, implementation and evaluation. The aim of this study was to determine the effect of counterpreasure techniques and deep breathing relaxation techniques on labor pain in women giving birth during the first active phase at Dr. Hospital. Hafiz Cianjur. This research method uses a pre-experimental research design with a one group pretest-posttest design approach. The sampling technique used was a purposive sampling technique, with a sample of 20 respondents in this study. Data analysis for this study used the Wilcoxon test. The results of the research show that there is an influence of Counterpressure and Deep Breathing Relaxation Techniques before and after on the pain of childbirth, seen from the p-value of 0.000, which means <0.005, so it can be concluded that there is an influence or difference in the level of pain in childbirth in mothers giving birth during the 1st active phase in the delivery room. Dr. Hafiz Cianjur in 2023. The conclusion of this research is that there is an influence of counterpressure and deep breathing relaxation techniques on childbirth pain in women giving birth during the first active phase at Dr Hafiz Cianjur Hospital in 2023.